HYALOCHITON KOMAROFFII (JAKOVLEV) (HETEROPTERA: TINGIDAE) FIRST RECORD IN SERBIA (Acta Entomologica Serbica, 2017)
First record of tingid Hyalochiton komaroffii (Jakovlev, 1880) in Serbia at Ibarska Klisura gorge, at locality Maglič.